ECONOMIC AND POLITICAL PROBLEMS OF THE MIDDLE EAST COUNTRIES, SECURITY POLICIES OF THE REGIONAL STATES (International Journal of Innovative Technologies in Economy, 2026)
States have advantages and disadvantages based on their location and geographical features on the world map. Its geostrategic location necessitates the more effective and careful use of national power elements to protect states’  national interests and achieve its national goals. The aim of this study is to comprehensively examine the new threat and risk assessments made on different platforms for the Middle East; to investigate the security concerns created by the process of physically and politically changing the world map based on cultural, ethnic, religious, and sectarian grounds; and to reveal how other states, situated in the middle of a potential crisis region due to its geostrategic location, will be affected by this change. The importance of the subject stems from the belief that the survival of the states  and their  ability to become a regional actor depends on properly evaluating developments in the Middle East and Eastern Mediterranean. The theoretical framework of this study is formed by constructivism (social constructivism), the theory that initiated the process of changing the world map and is based on the argument that the world is socially constructed, and the "Greater Middle East and North Africa Project (GMEAP)". In light of the available resources and interpretations in the study, a descriptive/descriptive approach was followed using content and discourse analysis, a qualitative research method, in order to create a conceptual, theoretical, and historical framework. The data used, the events in the historical process, theories/theses that gained or lost importance periodically, and the impact of the interaction between practice and theory on the Middle East and Eastern Mediterranean region are presented holistically using a descriptive method.